THE ABILITY OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN IMPLEMENTING THE CURRICULUM AT `AISYIYAH TSANAWIYAH MADRASAH PASAR MERAH MEDAN - Wahyuni, Sri; Amini, Nur Rahmah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Education is the most important part of the process of transforming knowledge from educators to students. Teachers act as the frontline in the scope of the world of education which is very important in determining the quality of generations. In the world of education, the curriculum is the spirit that must be evaluated innovatively, dynamically and periodically according to the development of the times and science and technology which is equivalent to the competency demands needed by society and the world of education. In Indonesia, the curriculum has undergone several changes and one of them is the curriculum. The main purpose of this change is for the improvement of a good and quality educational institution with the aim of the progress of a nation and state. This research uses qualitative descriptive analysis methods and data techniques which include data condensation, data presentation and conclusion making. This study aims to explain the analysis of the concept and implementation of the Curriculum. This curriculum is implemented by several schools that have been appointed by the government called piloting schools in Indonesia in accordance with Decree Number: 3374/KEP/D/KR/2016 dated July 11, 2016.